Buckling and postbuckling of architectured materials: A review of methods for lattice structures and metal foams - Völlmecke, Christina; Todt, Melanie; Yiatros, Stylianos (My University, 2021)
Recent advances in manufacturing and material science have given rise to numerous architectured materials (archimats), which are tailored for multifunctionality and improved performance. Specifically, lattice structures and metal foams are usually lightweight optimized structural morphologies, which are prone to non-linear instability phenomena, leading to collapse or to a different stable state. This article offers an extensive review of analytical, numerical and experimental methods for investigating buckling and postbuckling in such materials. In terms of analytical modelling, linear elastic and geometrically non-linear models are presented. In numerical analysis, discrete and continuum models are presented, highlighting how numerical modelling can inform design of such materials and finally, experimental methods across different scales are reported, highlighting their merits, depending on the aim of the investigation.
Keywords: Architectured materials; Buckling; Postbuckling; Analytical model; Finite element method; Experiments